Design and optimization of PV / wind hybrid power system for remote telecommunication station - Tunku Muhammad Nizar, Tunku Mansur (Curtin University of Technology, 2014)
The objective of this research is to design and optimization of the hybrid power system for powering remote telecommunication station. The base transceiver station (BTS) made by VNL of India has a lower power rating and reliable for outdoor environment hence a good solution for stand alone application. The design process includes selected site assessment, determining the system sizing, configuration and cost analysis. HOMER software is used to simulate and verify the result to find the feasible design configuration and cost optimization.